P224 Responder definitions for the ulcerative colitis Patient-Reported Outcomes Signs and Symptoms (UC-PRO/SS) tool using patients with ulcerative colitis treated with etrolizumab. (25th January 2019) - Higgins, P; Matsui, A; DeBusk, K; Pulley, J; Scalori, A; Oh, Y S; Arulmani, U
Abstract: Background: Patient-reported outcomes (PROs) are important for evaluating treatment efficacy; there is a need to define what is a clinically meaningful change in PROs. The UC-PRO/SS is the first PRO to undergo a rigorous development process outlined by health authorities, with input from patients and clinical experts. 1 Responder definitions for the UC-PRO/SS may allow for it to be a valuable tool for use in clinical trials and practice. We propose responder definitions for the UC-PRO/SS using patients treated with etrolizumab from the Phase 3 open-label induction cohorts of HICKORY (NCT02100696) and LAUREL (NCT02165215). Methods: Analysis included patients with moderate to severe ulcerative colitis (UC) who were treated with etrolizumab 105 mg every 4 weeks during a 10- or 14-week induction period. The UC-PRO/SS consists of 2 separately scored scales: a 3-item functional symptoms domain and 6-item bowel signs and symptoms domain (Table 1). The domain score is equal to the sum of the items (0–12 for functional and 0–27 for bowel; no combined total score). Item scores were calculated as an average of 4–7 days during a 9-day window before follow-up. Minimum clinically meaningful differences were calculated using distributional- and anchor-based methods. Responder definitions were triangulated from the anchor-based thresholds based on a reduction of ≥ 16 points in the inflammatory bowel disease Questionnaire and > 3 points in the full Mayo Clinic Score at Week 10 or 14. Results: As of May 2018, 218 patients (38% aTNF-experienced) provided a baseline UC-PRO/SS response (Table 2). The anchor methodology provided a range for the minimum clinically meaningful change of 1.48–2.07 for the functional domain and a range of 4.85–6.31 for the bowel domain. From these ranges, responder definitions of a reduction ≥ 1.5 points in the functional domain and ≥5 points in the bowel domain were determined through triangulation. Using these cut-offs, 56% of patients were responders according to the functional domain and 62% according to the bowel domain. Conclusions: Preliminary definitions for response to treatment using the UC-PRO/SS are a reduction of ≥ 1.5 points in the functional domain or ≥5 points in the bowel domain. These cut-offs will be confirmed in the ongoing Phase 3 UC placebo-controlled studies. References 1 Higgins PDR, Harding G, Revicki DA, et al., (2017), Development and validation of the ulcerative colitis patient-reported outcomes signs and symptoms (UC-pro/SS) diary, J Patient Rep Outcomes, 26